Strengthening Afforestation Efforts through Environmnetal Awareness Creation in Rivers State. (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Forests play a vital role in sustaining livelihoods, biodiversity, and climate stability, yet in Rivers State, Nigeria, rapid deforestation threatens these benefits. This paper examines the critical role of environmental education and awareness creation in strengthening afforestation efforts and promote sustainable forest management in Rivers State. It emphasises the growing threats of deforestation, environmental degradation and climate change and argues that limited public awareness remains a major barrier to sustainable forest management. Based on existing literature and circumstances in Rivers State, the paper highlights the need for a people-centered approach that goes beyond tree planting to foster environmental stewardship among communities, Five key suggestions were proposed as a call to action amongst which were: that there should be an implementation of comprehensive environmental education programmes at all levels of society, including schools, communities, and workplaces by the Rivers State Ministries of Education, Agriculture and Forestry; that there should be an advocacy for the development and implementation of policies that incentivise afforestation and sustainable forest management practices; that there should be a facilitation of collaboration and partnerships between governments, non-governmental organisations, businesses, and international stakeholders to support afforestation initiatives and promote forest conservation globally. By implementing these suggestions, we can harness the transformative power of environmental awareness to address the urgent challenges facing forests and pave the way towards a more sustainable and resilient future for all.